Bagus PEMETAAN BIDANG TANAH BERBASIS PROGRAM PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI WILAYAH DESA DAWAN KLOD, KECAMATAN DAWAN, KABUPATEN KLUNGKUNG - Ariwijaya, Dewa; Treman, I Wayan; Putra, I Wayan Krisna Eka (Jurnal ENMAP (Environment and Mapping), 2024)
The need for land increases with population growth and development, while land area is limited. The PTSL program aims to simplify city planning and ensure land certificates are given to the right parties, such as fishermen and farmers, to improve their quality of life. Certified land cannot participate in this program. This research aims to determine the implementation of PTSL in Dawan Klod Village, Klungkung Regency, using qualitative methods to understand social and contextual aspects. The research results show that the PTSL program in the village is running well, even though there are obstacles such as limited ASN BPN survey officers and participation of village leaders. In Dawan Klod Village, 1,697 plots of land covering an area of ​​229.60 Ha have been mapped, while 505 plots of land covering an area of ​​103.36 Ha have not been mapped.